Exploring Students' Difficulties in Writing Undergraduate Thesis: A Case Study in a Private Islamic University - Siti Rahma Sari; Harlina Harja; Sri Hidayati; Dzakiyah Ramadhanianty (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2025)
The aim of this study was to investigate the difficulties and solutions that students faced when writing their undergraduate theses. To provide rich sources of data on individuals' experiences, the researcher designed the research using qualitative method with a case study approach. This study included ten individuals who satisfied the research's inclusive requirements, such as being active learners, having completed the thesis seminar stage, and being willing to freely participate in this study. The researchers collected data using semi-structured interviews. The data was then analyzed by using thematic analysis (coding). The findings revealed four themes of challenges: linguistics and writing knowledge issues (grammar, vocabulary, paraphrasing, and referencing), psychological issues (lack of motivation and confidence), media and resource issues (online platform, limited references, and inaccessible websites), and supervision and time management issues (unsupportive supervisor and poor time management). This study also discovered three strategies used by students to reduce those challenges: self-management strategies (doing positive activities and taking schedule notes), technological aids (language apps and entertainment/studying apps), and assistance from others (supervisors, families, and friends).